2017
DOI: 10.1039/c7ra05803a
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent optical and thermochromic properties of Sm3Fe5O12

Abstract: Reversible thermochromic inorganic materials of Sm3Fe5O12with different particle sizes have been synthesized by a conventional high temperature solid state reaction method (2.51 μm) and sol–gel method (0.16 μm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Electrons need more energy to transition from the valence band to the conduction band, thus increasing the bandgap again, leading to the cutoff wavelength blueshift, and then the absorption in the visible band is reduced, so at last the color of the coating achieves complete recovery. This is similar to the thermochromism of rare-earth iron garnet 18,23 and lead-free halide double perovskites. 45 Meanwhile, the coefficient of thermal expansion (CTE) can be acquired by using the formula below:…”
Section: Lattice and Bandgap Evolutionsupporting
confidence: 70%
See 1 more Smart Citation
“…Electrons need more energy to transition from the valence band to the conduction band, thus increasing the bandgap again, leading to the cutoff wavelength blueshift, and then the absorption in the visible band is reduced, so at last the color of the coating achieves complete recovery. This is similar to the thermochromism of rare-earth iron garnet 18,23 and lead-free halide double perovskites. 45 Meanwhile, the coefficient of thermal expansion (CTE) can be acquired by using the formula below:…”
Section: Lattice and Bandgap Evolutionsupporting
confidence: 70%
“…Significant thermochromism, clear colortemperature correspondence, and high-temperature stability are important prerequisites for noncontact temperature measurement using thermochromic material. However, all of the materials mentioned above have their limitations, vanadium oxide and molybdenum oxides mainly change color below 300 • C 21,22 ; rare-earth garnet structural oxide has good thermal stability but their visible spectra do not differ significantly at different temperatures, which indicates that the thermochromism is not significant 18,23 ; transition metal-doped oxide exhibit thermochromism at higher temperature (such as Y-doped Bi 2 O 3 20 at 20-777 • C, Co-doped ZnO 24 at 25-800 • C, and Co-doped TiO 2 25 at 20-800 • C), but their color-temperature correspondence has not been clearly explored. Recently, Yuan et al 26 have reported that the CIE-L × ab parameter can be described as a function of temperature for Fe/Cr-(co)doped α-Al 2 O 3 , but the function is close to a horizontal line and has a large error, which limits its further application.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides such as TiO2, ZnO, WO3 and VO2 exhibit thermochromic effect in the visible area. Some oxides including V2O5, nanoparticles of VO2, Co-doped zinc oxide, and metamaterials exhibit thermochromic characteristics in the near-infrared region [4,9,11,14,[21][22][23][24][25][26][27][28]. Garnets are a well-known kind of magnetic oxides that are utilized in radars, telecommunications, RF measuring systems, and microwave devices such as circulators, isolators, phase shifters, and tunable filters.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its importance in magneto-optical and microwave devices, Yttrium iron garnets (YIG) is an intriguing ferrimagnetic oxide [29][30][31][32][33][34][35]. Several groups have explored the optical properties of garnet single crystals, thin films, and powders [22,23,33,34,[36][37][38][39]. The presence of Fe 3+ ions in iron oxides generally results in red coloration in Fe3O4, Fe2O3, ZnFe2O4 and MgFe2O4, however it results in a comparatively green coloration in YIG.…”
Section: Introductionmentioning
confidence: 99%
“…Deka et al synthesized the Y 3−x Sm x Fe 5 O 12 system with x = 0.0 to 3.0 of pure phase by the solid-state reaction method with synthesis temperatures of 1400 ºC in the year 2017 8 . Also, in 2017 they reported the synthesis of Sm 3 Fe 5 O 12 with a calcination temperature of 1200 ºC and a sintering temperature of 1400 ºC 9 . In the same year Jang et al reported the synthesis of Y 3 Fe 5 O 12 obtained by the sol-gel method with a temperature of 1400 ºC 10 ; similarly, Tholkappiyan et al reported the same sintering temperature for dysprosium iron garnet (Dy 3 Fe 5 O 12 ), showing the formation of thick and pure phase microstructures 11 .…”
Section: Introductionmentioning
confidence: 99%